IoT-Based Smart Locker: Innovation in Automatic Package Receipt Integrated with Telegram - Elvinda Bendra Agustina; Recha Nofillah (TELKA - Telekomunikasi Elektronika Komputasi dan Kontrol, 2026)
The development of E-Commerce in this digital era is increasingly rapid, thus affecting the use of goods delivery services. The problem that often occurs in the delivery process is that the recipient of the goods is traveling. This automatic Smart box system is designed to receive packages automatically remotely using the internet of things via the Telegram application. The system uses an ultrasonic sensor to send notifications to the Telegram bot if a package arrives by reading a distance value between 10 cm. This system also utilizes a servo motor as an actuator that can be controlled to open and close the package box. Meanwhile, to find out if the package has been placed in the package box, a load cell sensor is used to send the package weight value. This system uses an ESP32 microcontroller as the system control center and WiFi network. The system is also equipped with ESP32-CAM which is used as a security tool when goods arrive. The test results show that the tool can work well and all components can run according to their function, and connect to the Telegram bot. However, problems that are sometimes encountered are problems that may occur in the system, namely internet network problems that affect sending messages to the Telegram bot.